Reduction of defects on microstructure aluminium nitride using high temperature annealing heat treatment - Tanasta, Z.; Muhamad, Pauziah; Kuwano, Noriyuki; Mohd Yatim, Norfazrina Hayati; Unuh, Mohd Hishamuddin (Institute of Physics Publishing, 2018)
Aluminium Nitride (AlN) is a ceramic 111-nitride material that is used widely as components in functional devices. Besides good thermal conductivity, it also has a high band gap in emitting light which is 6 eV. AlN thin film is grown on the sapphire substrate (0001). However, lattice mismatch between both materials has caused defects to exist along the microstructure of AlN thin films. The defects have affected the properties of Aluminium Nitride. Annealing heat treatment has been proved by the previous researcher to be the best method to improve the microstructure of Aluminium Nitride thin films. Hence, this method is applied at four different temperatures for two hour. The changes of Aluminium Nitride microstructures before and after annealing is observed using Transmission Electron Microscope. It is observed that inversion domains start to occur at temperature of 1500 ℃. Convergent Beam Electron Diffraction pattern simulation has confirmed the defects as inversion domain. Therefore, this paper is about to extract the matters occurred during the process of producing high quality Aluminium Nitride thin films and the ways to overcome this problem.